The worst class in school (Wayland, 1999)
Join the Worst Class on their chaotic journey through a landscape of naughtiness. A disastrous museum visit, a worryingly enthusiastic chemistry lesson and the trials of the school caretaker, not to mention choir practice and a host of other bits of bad behaviour, finally lead to their teacher's resignation poem.